Pengembangan Asesmen Otentik Kurikulum 2013 dengan Menggunakan Analisis Video Pelaksanaan Pembelajaran Berbasis Konteks di Madrasah Ibtidaiyah - Kholifah, Nur (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2019)
This research had purpose to produce of the curicullum authentic 2013 applied to science learning, and its learning instrument through the PBL (Project Based Learning) model. Learning tools developed consists of lesson plans, activity sheets Learners, Creativity Test, and test results of Cognitive Learning. This type of research was the research development. The development of model used was 4-D (Four-D Model) that were developed become 3D, the procedure consisting of stages of defining , designing, and development. The subjects of this reserch were students in the fourth grade in Darul Huda Madrasa Ibtidaiyah (experiment 1), Hasanuddin II Madrasa Ibtidaiyah, and At Taqwa Madrasa Ibtidaiyah (experiment 2) with the design of the research one group pretest-posttest design. The collecting data used the were observation method, tests, and questionnaires. The data analysis technique were quantitative descriptive analysis. The result of the research showed that: (a) the response of students towards learning were positive (the average percentage of student who were interested in learning to experiments 1 and 2 were 93% an 95%; (b) implemention to the learning instrument for good learning (average percentage of experiments 1 and 2 are were 91% and 96%); (c) obstacles that was encountered during the learning can be good resulted overcome by the teacher with some solutions; (d) the average result of the creativity n-gain; Darul Huda Madrasa Ibtidaiyah 0,7, Hasanuddin Madrasa Ibtidaiyah 0,9 dan At Taqwa Wotgalih Madrasa Ibtidaiyah 0,8 (e) all of students completed their study results in individual and classical, all of students completed their study in individual results in class as 95 (experiment 1), 93 and 94 (experiment 2). Then their study in class results in class is 100% (experiments 1 and 2). Based on the research of result we concluded that curicullum authentic 2013 and learning instrument were proper, practical and effective way to enhance creativity and learning outcomes of students Madrasa Ibtidaiyah.